Rates of Return on Human and Non-Human Capital in Africa's Manufacturing Sector. - Bigsten, A; Collier, P; Dercon, S; Fafchamps, M; Gauthier, B; Gunning, J; Isaksson, A; Oduro, A; Oostendorp, R; Pattillo, C; Söderbom, M; Teal, F; et al. (CSAE (University of Oxford), 1998)
In this paper two sets of issues are addressed using panel data from the manufacturing sector of five African countries. First, how high are the returns to human relative to physical capital. Second, what is the relative importance of technology and endowments of human and physical capital in determining differences in earnings and productivity across the countries. Evidence from earnings functions shows that the private returns to both experience and education rise with the level of education. Private returns rise from 3 per cent at the primary level, to 10 per cent at the secondary level and 35 per cent for tertiary. Evidence from the production function gives lower returns on education than from the earnings function. Rates of return on physical capital exceed 20 per cent and greatly exceed the average return on human capital. Data is available on the stocks of human and physical capital across the countries. Productivity and earnings differentials are shown to be large between Cameroon and Ghana. These differences are due almost entirely to differences in physical, not human, capital endowments.